2022
DOI: 10.3390/jcm11195936
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Microbiota Gut–Liver Axis during HCV Chronic Infection: A Schematic Overview

Abstract: Hepatitis C virus (HCV) still represents one of the most important worldwide health care problems. Since 2011, direct-acting antiviral (DAA) drugs have increased the number of people who have achieved a sustained virological response (SVR). Even if the program to eradicate HCV by 2030 is still ongoing, the SARS-CoV-2 pandemic has created a delay due to the reallocation of public health resources. HCV is characterized by high genetic variability and is responsible for hepatic and extra-hepatic diseases. Dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…Similar changes (growth of Bacilli and Proteobacteria and decreased abundance of Clostridia) are observed in HCV infection [51,85,86], which presents in 0.7% of the population [1]. Endotoxemia, which indicates molecular bacterial translocation, is also observed in chronic hepatitis C [85][86][87]. In chronic HBV infection, which affects approximately 300 million people worldwide [1], a decrease in the content of Clostridia and the growth of Bacilli were observed in the gut microbiota.…”
Section: Gut Microbiota and Intestinal Barrier In Chronic Liver Disea...mentioning
confidence: 80%
See 1 more Smart Citation
“…Similar changes (growth of Bacilli and Proteobacteria and decreased abundance of Clostridia) are observed in HCV infection [51,85,86], which presents in 0.7% of the population [1]. Endotoxemia, which indicates molecular bacterial translocation, is also observed in chronic hepatitis C [85][86][87]. In chronic HBV infection, which affects approximately 300 million people worldwide [1], a decrease in the content of Clostridia and the growth of Bacilli were observed in the gut microbiota.…”
Section: Gut Microbiota and Intestinal Barrier In Chronic Liver Disea...mentioning
confidence: 80%
“…Similar changes (growth of Bacilli and Proteobacteria and decreased abundance of Clostridia) are observed in HCV infection [51,85,86], which presents in 0.7% of the population [1]. Endotoxemia, which indicates molecular bacterial translocation, is also observed in chronic hepatitis C [85][86][87].…”
Section: Gut Microbiota and Intestinal Barrier In Chronic Liver Disea...mentioning
confidence: 82%
“…Gut dysbiosis is a medical condition that happens when there is a microbial imbalance in a person's intestines. Gut microbiota or their metabolites improve or aggravate the progression of multiple liver diseases such as chronic hepatitis B virus (HBV), 34 chronic hepatitis C virus (HCV), 35 NAFLD, 36 ALD, 37 other-induced liver disease 38 and HCC 39 (Fig. 2) through several mechanisms, 40 including changes in the intestinal permeability, 41 short-chain fatty acids (SCFAs), 42 long-chain fatty acids (LCFAs), 43 fastinginduced adipocyte factor (FIAF), choline metabolism, 44,45 ethanol production, 46 and BAs metabolism 47,48 (Fig.…”
Section: Mechanisms Linking the Gut-liver Axismentioning
confidence: 99%
“…After receiving direct-acting antiviral therapy, nonindigenous and pathogenic taxa, including Enterobacteriaceae, Staphylococcus , and Enterococcus , decreased in the gut of cirrhotic individuals with hepatitis C. Nonetheless, a recent study found that HCV patients did not have significant GM changes, and HCV eradication with direct-acting antivirals was not associated with significant and beneficial modulation of intestinal microbiota. 20 21 Table 1 depicts the key features associated with GM changes in HBV and HCV infection.…”
Section: Role Of Gut Microbiota In Liver Diseasementioning
confidence: 99%